Cell death induced by NLRP3–palmitate axis impairs pulmonary damage tolerance and aggravates immunopathology during obesity-tuberculosis comorbidity - Palma Albornoz, Sandra P; Fraga-Silva, Thais FC; de Carvalho, Renan VH; Rodrigues, Tamara S; Gembre, Ana Flávia; de Oliveira, Rômulo Silva; de Souza, Fernanda Mesquita; Corrêa, Giseli Furlan; Ramalho, Leandra NZ; Carlos, Daniela; de Almeida, Danilo C; Câmara, Niels OS; et al. (Wiley, 2023)
A low-grade and persistent inflammation, which is the hallmark of obesity, requires the participation of NLRP3 and cell death. During Mycobacterium tuberculosis infection, NLRP3 signaling is important for bacterial killing by macrophages in vitro but was shown to be dispensable for host protection in vivo. We hypothesized that during obesity-tuberculosis (TB) comorbidity, NLRP3 signaling might play a detrimental role by inducing excessive inflammation. We employed a model of high-fat-diet-induced obesity, followed by M. tuberculosis infection in C57BL/6 mice. Obese mice presented increased susceptibility to infection and pulmonary immunopathology compared to lean mice. Using treatment with NLRP3 antagonist and Nlrp3−/− mice, we showed that NLRP3 signaling promoted cell death, with no effect in bacterial loads. The levels of palmitate were higher in the lungs of obese infected mice compared to lean counterparts, and we observed that this lipid increased M. tuberculosis-induced macrophage death in vitro, which was dependent on NLRP3 and caspase-1. At the chronic phase, although lungs of obese Nlrp3−/− mice showed an indication of granuloma formation compared to obese wild-type mice, there was no difference in the bacterial load. Our findings indicate that NLRP3 may be a potential target for host-directed therapy to reduce initial and severe inflammation-mediated disease and to treat comorbidity-associated TB. © 2022 The Pathological Society of Great Britain and Ireland.
Keywords: cell death; host-directed therapy; immunopathology; Mycobacterium tuberculosis; NLRP3; obesity